Pressure stability of the first hydration shell of yttrium in aqueous YCl3 solution. Issue 1 (2nd January 2020) - Elbers, M.; Sternemann, C.; Julius, K.; Paulus, M.; Surmeier, G.; König, N.; Nase, J.; Bolle, J.; Wagner, R.; Irifune, T.; Tolan, M.
ABSTRACT: The pressure stability of the first hydration shell of Y 3 + ions in aqueous solution has been investigated by means of extended x-ray absorption fine-structure spectroscopy at the yttrium K-edge for hydrostatic pressures up to 4.5 kbar and concentrations between 1 M and 2.5 M. We find approximately 8.4 water molecules surrounding the yttrium cation at a mean distance of 2.370 Å at ambient conditions, independent on the concentration. The yttrium hydration shell has a low compressibility in the order of ( − 3.8 ± 0.7 ) × 10 − 4  Å kbar − 1 emphasizing its pressure stability in the kbar range. At the studied conditions, no indication for chloride complexation was observed.